A Role for CD154, the CD40 Ligand, in Granulomatous Inflammation. (12th July 2017) - Villeneuve, Julien; Desmoulière, Alexis; Dewitte, Antoine; Bordeau, Nelly; Costet, Pierre; Bassaganyas, Laia; Fricain, Jean-Christophe; Ripoche, Jean; Lepreux, Sébastien
Abstract : Granulomatous inflammation is a distinctive form of chronic inflammation in which predominant cells include macrophages, epithelioid cells, and multinucleated giant cells. Mechanisms regulating granulomatous inflammation remain ill-understood. CD154, the ligand of CD40, is a key mediator of inflammation. CD154 confers a proinflammatory phenotype to macrophages and controls several macrophagic functions. Here, we studied the contribution of CD154 in a mouse model of toxic liver injury with carbon tetrachloride and a model of absorbable suture graft. In both models, granulomas are triggered in response to endogenous persistent liver calcified necrotic lesions or by grafted sutures. CD154-deficient mice showed delayed clearance of carbon tetrachloride-induced liver calcified necrotic lesions and impaired progression of suture-induced granuloma. In vitro, CD154 stimulated phagocytosis of opsonized erythrocytes by macrophages, suggesting a potential mechanism for the altered granulomatous inflammation in CD154KO mice. These results suggest that CD154 may contribute to the natural history of granulomatous inflammation.